aPPRove: an HMM-based method for accurate prediction of RNA-pentatricopeptide repeat protein binding events - Harrison, Thomas, author; Boucher, Christina, advisor; Ben-Hur, Asa, committee member; Sloan, Daniel, committee member (Colorado State University. Libraries, 2015)
Pentatricopeptide repeat containing proteins (PPRs) bind to RNA transcripts originating from mitochondria and plastids. There are two classes of PPR proteins. The P class contains tandem P-type motif sequences, and the PLS class contains alternating P, L and S type motif sequences. In this paper, we describe a novel tool that predicts PPR-RNA interaction; specifically, our method, which we call aPPRove, determines where and how a PLS-class PPR protein will bind to RNA when given a PPR and one or more RNA transcripts by using a combinatorial binding code for site specificity proposed by Barkan et al. [1]. Our results demonstrate that aPPRove successfully locates how and where a PPR protein belonging to the PLS class can bind to RNA. For each binding event it outputs the binding site, the amino-acid-nucleotide interaction, and its statistical significance. Furthermore, we show that our method can be used to predict binding events for PLS-class proteins using a known edit site and the statistical significance of aligning the PPR protein to that site. In particular we use our method to make a conjecture regarding a novel binding event between CLB19 and the second intronic region of ycf3. The aPPRove web server can be found at www.cs.colostate.edu/~aPPRove and the soft- ware is available at that website for stand alone usage.
Keywords: PPR; HMM